2002
DOI: 10.1002/ajmg.a.10011
|View full text |Cite
|
Sign up to set email alerts
|

Novel missense mutations and a 288‐bp exonic insertion in PAX9 in families with autosomal dominant hypodontia

Abstract: We describe the molecular analysis of three families with hypodontia involving primarily molar teeth and report two novel mutational mechanisms. Linkage analysis of two large families revealed that the hypodontia was linked to the PAX9 locus. These two families revealed missense mutations consisting of a glutamic acid substitution for lysine and a proline substitution for leucine within the paired domain of PAX9. A pair of identical twins affected with hypodontia in a third family demonstrated a 288-bp inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 12 publications
2
93
0
Order By: Relevance
“…12,14 In humans, dominant mutations in PAX9 have been identified as a cause of congenital absence of some posterior (and occasionally anterior) teeth. Frame-shift, [15][16][17] insertion, 18,19 missense 18 and non-sense 20,21 mutations, as well as whole-gene deletion, 18,22,23 have been described in families exhibiting hypodontia, primarily with absence of molar teeth. In addition, it has been shown that common polymorphisms in PAX9 are associated with 3rd molar (M3) agenesis.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 In humans, dominant mutations in PAX9 have been identified as a cause of congenital absence of some posterior (and occasionally anterior) teeth. Frame-shift, [15][16][17] insertion, 18,19 missense 18 and non-sense 20,21 mutations, as well as whole-gene deletion, 18,22,23 have been described in families exhibiting hypodontia, primarily with absence of molar teeth. In addition, it has been shown that common polymorphisms in PAX9 are associated with 3rd molar (M3) agenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest the PAX9 mutant phenotype is dosage dependent: deletion of the PAX9 locus manifests as missing permanent teeth and the entire primary dentition; 10 missense mutations result in oligodontia of only the permanent teeth; 6,8,13,21 other mutations that would encode a truncated polypeptide present with missing permanent teeth, as well as some primary teeth. 5,7 -11 These findings, however, fail to fully explain the mechanisms underlying disease-causing mutations that result in less severe and variable phenotypes where not all posterior teeth are affected.…”
Section: Discussionmentioning
confidence: 99%
“…15,33 Heterozygous deletion of the entire Pax9 gene has also been reported in severe hypodontia involving the primary and permanent molars in a small nuclear family. 19 The absence of mutations in the coding regions of either Pax9 or Msx1, in some patients with oligodontia indicated that other genes encoding transcription factors might be responsible for the patterning of the dentition. 15 A study of non-syndromic oligodontia in a multigenerational family detected no mutation within the coding region of Msx1, though total exclusion of this locus was not carried out.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Three articles on hypodontia in triplets 18,20,21 were found using a PubMed search and none described hypodontia of the severity seen in the patients in this case report. This article describes a case involving a set of triplets with severe hypodontia, affecting molars, premolars and incisors.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%